Exploring cognitive and emotional symptoms associated with hippocampal subfield atrophy in drug-induced Parkinsonism - Zhou, Wei; Tang, MengYue; Cheng, Bo; Sun, Ling; Lin, HongYu; Fan, Yang; Liu, Nian; Zhang, Shushan (Frontiers in Aging Neuroscience, 2025)
BackgroundDrug-induced Parkinsonism (DIP) is a secondary Parkinsonism with limited research on its hippocampal structural changes. This study explores hippocampal subfield volumes in DIP compared to Parkinson’s disease (PD) and healthy controls (HCs), investigating correlations with cognitive (Montreal Cognitive Assessment, MoCA), emotional (Hamilton Depression Rating Scale, HAMD; Hamilton Anxiety Rating Scale, HAMA), and motor (Unified Parkinson’s Disease Rating Scale, UPDRS) symptoms.MethodsA total of 19 DIP patients, 20 PD patients, and 20 HCs were enrolled. MRI-based hippocampal subfield volumes were assessed using FreeSurfer, and clinical scores were evaluated for cognitive, emotional, and motor functions. Statistical analyses compared group differences and examined correlations.ResultsSignificant atrophy was observed in the DIP group in multiple hippocampal subfields compared to HCs, including the presubiculum, subiculum, Granule cell and molecular layer of the dentate gyrus (GC-ML-DG), molecular_layer_HP, Cornu ammonis (CA) 1, CA4, hippocampal tail, and fimbria. MoCA scores positively correlated with volumes in bilateral hippocampus and subfields such as subiculum and CA4, while HAMD scores mainly showed negative correlations in both DIP and PD group. UPDRS scores revealed group-specific patterns, with DIP showing stronger associations between non-motor symptoms and hippocampal volume.ConclusionThis study first reported significant hippocampal subfield atrophy in DIP, distinct from PD, and links structural changes to cognitive, emotional, and motor impairments. These findings advance understanding of DIP pathophysiology and underscore the hippocampus’s role in non-motor symptoms.